2015
DOI: 10.1161/hypertensionaha.115.06091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ivabradine on Central Aortic Blood Pressure and Myocardial Perfusion in Patients With Stable Coronary Artery Disease

Abstract: Abstract-Treatment of hypertensive patients with β-blockers reduces heart rate and decreases central blood pressure less than other antihypertensive drugs, implying that reducing heart rate without altering brachial blood pressure could increase central blood pressure, explaining the increased cardiovascular risk reported with β-blocker. We describe a randomized, double-blind study to explore whether heart rate reduction with the I f inhibitor ivabradine had an impact on central blood pressure. We included 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
0
19
2
4
Order By: Relevance
“…23 This in turn was presumably the principle reason in ASCOT for atenololbased therapy being less efficacious than amlodipine-based therapy in reducing morbidity and mortality. 24 Our findings are apparently in contrast with the recently published study of Dillinger et al, 25 who in controlled hypertensive patients with CAD failed to observe an increase in central pressure after HR reduction with ivabradine. This could be explained by some important clinical and methodological differences between their study and our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…23 This in turn was presumably the principle reason in ASCOT for atenololbased therapy being less efficacious than amlodipine-based therapy in reducing morbidity and mortality. 24 Our findings are apparently in contrast with the recently published study of Dillinger et al, 25 who in controlled hypertensive patients with CAD failed to observe an increase in central pressure after HR reduction with ivabradine. This could be explained by some important clinical and methodological differences between their study and our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study demonstrated a significant decrease in diastolic blood pressure in patients with HCM. Interestingly, this differs from results of former studies that did not observe an effect of ivabradine on blood pressure [23]. The reason for this discrepancy is not clear, but a diastolic dip of blood pressure might be the result of the prolonged diastole with increased preload.…”
Section: Discussioncontrasting
confidence: 97%
“…Prior studies have suggested that β-blockers can increase pulse wave reflections/arterial stiffness, thereby negating the blood-pressure-lowering effects on cardiovascular mortality and specifically precluding the reduction of central aortic blood pressure, which may be attributable in part to heart rate reduction [17]. However, a cross-over study specifically examining ivabradine versus β-blockers showed no effect of ivabradine on central aortic pressure [18]. Therefore, central pulse wave reflections and blood pressure effects are unlikely to explain the results of SIGNIFY or to negate the results of SHIFT in patients with CAD with or without angina.…”
Section: Discussionmentioning
confidence: 99%